2015
DOI: 10.1039/c5nr04424c
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic versus blocked states in aggregates of Fe3−xO4 nanoparticles studied by MFM

Abstract: Magnetic domain configurations in two samples containing small aggregates of Fe(3-x)O4 nanoparticles of about 11 and 49 nm in size, respectively, were characterized by magnetic force microscopy (MFM). Two distinct magnetic behaviors were observed depending on the particle size. The aggregates constituted of nanoparticles of about 11 nm in size showed a uniform dark contrast on MFM images, reflecting the predominant superparamagnetic character of these particles and arising from the coherent rotation of the spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…However, characterization of different properties, such as spatial distribution, size and magnetic behavior of single superparamagnetic nanoparticles is difficult to perform at ambient conditions and mostly a combination of different measurement techniques is needed. Magnetic force microscopy (MFM) proved to be a promising technique to successfully image clusters of small superparamagnetic nanoparticles without labelling and provides all the information described above in a single pass [7][8][9][10][11]. Recent investigations demonstrate the capability of MFM for biological systems e. g. to evaluate the iron distribution in biological tissues [12] and to study the cellular uptake of magnetic nanoparticles [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, characterization of different properties, such as spatial distribution, size and magnetic behavior of single superparamagnetic nanoparticles is difficult to perform at ambient conditions and mostly a combination of different measurement techniques is needed. Magnetic force microscopy (MFM) proved to be a promising technique to successfully image clusters of small superparamagnetic nanoparticles without labelling and provides all the information described above in a single pass [7][8][9][10][11]. Recent investigations demonstrate the capability of MFM for biological systems e. g. to evaluate the iron distribution in biological tissues [12] and to study the cellular uptake of magnetic nanoparticles [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of magnetic relaxation in magnetic soft materials [15][16][17][18] , the response to an AC magnetic field strongly depends on the type of the magnetic building blocks. Thus, for example, magnetic nanoparticles can be superparamagnetic or blocked 19,20 . In order to carefully control the properties of magnetic nanoparticles, many various approaches were recently proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the corresponding MFM phase and topographical images for bare as well as silica-coated SPIONs. A study in the Universitat de Barcelona in Spain demonstrated that MFM could be used to distinguish between superparamagnetic and blocked states in aggregates of iron oxide nanoparticles [21]. Another study used MFM to investigate the magnetic microstructure of nanoparticles with single-and multi-domain octahedral particles [22].…”
Section: Magnetic Force Microscopy For Nanoparticle Characterizationmentioning
confidence: 99%